Análisis de los factores que intervienen en el ámbito de la dirección que afectan al desempeño de los proyectos de desarrollo de software a la medida, tomando una muestra de las empresas que se involucran en sector bancario de la ciudad de Quito - Molina Vinueza, Mario Andrés (2014)
In recent years customized software development has grown significantly in Ecuador, consolidating itself as a strategic technological industry in its own right due to its pivotal role in modern business. While the quality of domestically produced customized software has gone so far as to find an incipient place among Ecuadorian export commodities, it is all the more vital to evaluate the current success rate and to identify the factors that challenge its future growth. Despite the good prospects for the software development industry in the country, it is always important to analyze the current situation to improve. Thus the need to know the percentage of successful projects that are achieved and what factors at the level of project management that limit the success of software development projects to the measure are determined...